Hiburan atau Ancaman? Pandangan Kritis terhadap Judi Online dalam Konteks Fatwa Majelis Ulama Indonesia (MUI) - Hikmawati, Hanifah (Kartika: Jurnal Studi Keislaman, 2024)
This article aims to explain the debate on action against online gambling related to the motivation of gamblers' actions and the laws underlying gambling. Some people argue that gambling is a legitimate form of entertainment for them. Some even consider gambling as a livelihood. On the other hand, gambling is an act that is prohibited and forbidden by religion and the state because of the negative impacts it causes. Online gambling can cause disease. The disease consists of two things: liver disease and social disease. There is a formulation of the problem to answer this article: first, how can the background of online gambling encourage the emergence of a desire for entertainment or even a threat? Second, how can the MUI Fatwa contribute to critical thinking about online gambling? The descriptive qualitative method aims to determine the phenomenology that occurs in society. One of them is the phenomenon of online gambling, especially in the Ngawi community. This article focuses on cases of online gambling that have been uploaded in the news on websites and social media, with the intent and purpose of entertainment or threats using the critical approach of the MUI fatwa. The Indonesian Ulama Council (MUI), in addition to being a unifying forum for Muslims, also plays a role in directing Muslims who are in contact with socio-cultural changes. The results of this article reveal that to overcome online gambling cases in Ngawi Regency, several mass organizations and the government have carried out the "Stop Online Gambling" Movement, which is socialized by agencies or mass organizations in Ngawi Regency. It is hoped that it can control the rate of increase in gambling perpetrators. This movement can reduce the impacts that occur due to gambling.